Analisis Hubungan Faktor Pengetahuan, Kepercayaan dan Sikap Terhadap Kepatuhan Pasien Dalam Melakukan Pengobatan Akupunktur - Kurniawan, Leny Candra; Diana, Sulis; Anggraeni, Dhonna (Universitas Malahayati, 2025)
ABSTRACT Patient compliance in following the therapist's recommendations regarding the therapy schedule is very important for the success of acupuncture therapy. The preliminary result that 63% of chronical disease of patient was not compliance to follow schedule of acupuncture treatment, so it can be prolong the healing process. To analysis the association of knowledge factors, belief, attitude toward patient compliance in acupuncture treatment. This study is an analytical observational study using a cross-sectional approach. The location of the study was at the Traditional Health Center of Sehat Harmoni Indonesia in Malang City in June-July 2024. The population in this study consisted of all 135 acupuncture patients. The research sample consisted of 102 patients who met the inclusion criteria and were selected using simple random sampling techniques. Data analysis used univariate, bivariate analysis with the Chi Square Test, and multivariate analysis with Multiple Logistic Regression. There were an association between knowledge on compliance with acupuncture treatment (p=0.000), variable of belief toward acupuncture treatment (p=0.000), variable of attitude towards acupuncture treatment (p=0.001). There was a simultaneous association between the factors of knowledge, beliefs, and attitude towards patient compliance in undergoing acupuncture treatment, where the knowledge factor was the main factor in compliance with acupuncture treatment. Factors that associated with patient compliance in undergoing acupuncture treatment in this place were patient knowledge, belief, and attitude towards acupuncture treatment. Keywords: Knowledge, Belief, Attitude, Compliace, Acupuncture ABSTRAK Kepatuhan pasien dalam mengikuti anjuran terapis tentang jadwal terapi menjadi hal yang sangat penting bagi keberhasilan terapi akupunktur. Diketahui hasil studi pendahuluan 63% pasien penyakit kronis tidak patuh menegikuti jadwal pengobatan akupunktur sehingga memperlama proses penyembuhan. Untuk Menganalisis hubungan faktor pengetahuan, kepercayaan, sikap terhadap kepatuhan pasien melakukan pengobatan akupunktur. Penelitian ini merupakan penelitian observasional analitik dengan menggunakan pendekatan cross-sectional. Lokasi penelitian di Balai Kesehatan Tradisional Sehat Harmoni Indonesia kota Malang bulan Juni-Juli 2024. Populasi dalam penelitian ini terdiri dari seluruh pasien akupunktur yang berjumlah 135 orang. Sampel penelitian terdiri dari 102 pasien yang memenuhi kriteria inklusi dan dipilih menggunakan teknik simple random sampling. Data dianalisis dengan menggunakan analisis univariabel, bivariabel, dan multivariabel. Hasil penelitian menunjukkan adanya hubungan antara tingkat pengetahuan dengan kepatuhan dalam menjalani pengobatan akupunktur (p=0,000), variabel kepercayaan terhadap kepatuhan pengobatan akupunktur (p=0,000), dan variabel sikap terhadap pengobatan akupunktur (p=0,001). Ada hubungan secara bersama-sama faktor pengetahuan, kepercayaan, dan sikap terhadap kepatuhan pasien dalam melakukan pengobatan akupunktur, dimana faktor pengetahuan sebagai faktor yang utama dalam kepatuhan melakukan pengobatan akupunktur. Faktor yang berhubungan dengan kepatuhan pasien dalam melakukan pengobatan akupunktur di tempat ini yaitu pengetahuan, kepercayaan, dan sikap pasien terhadap pengobatan akupunktur. Kata Kunci: Pengetahuan, Kepercayaan, Sikap, Kepatuhan, Akupunktur